OHVIRA Syndrome: A Case Report - Zeba, Dilruba; Zesmin, Fahmida; Roy, Rajib (Faridpur Medical College Journal, 2020)
OHVIRA syndrome or Herlyn-Werner-Wunderlich syndrome is a rare congenital anomaly of female urogenital tract which is represented by the triad of uterine didelphys, obstructed hemivagina and ipsilateral renal agenesis. This rare variant of Müllerian duct anomalies represent failure of vertical and the lateral fusion of Müllerian ducts around 9 weeks of gestation. OHVIRA syndrome comprises about 2-3% of Müllerian abnormalities. A 13 years old girl got admission in FMCH on 15.3.2018 with lower abdominal pain and acute retention of urine. Her menarche was established 6 months back with regular cycle and associated with dysmenorrhoea. Imaging studies revealed uterine didelphys, highly dilated cervix with hematocolpos and absence of right kidney. The vaginal septum was excised. The patient recovered fully and was under follow up for 6 months. There was no evidence of further outflow tract obstruction. Faridpur Med. Coll. J. Jan 2019;14(1): 54-56